Spatial Distribution of Genesis Malaria in Puskesmas Bontobahari Sub-District Bontobahari of Bulukumba District - Azriful Azriful; Alfida Syarif (HIGIENE: Jurnal Kesehatan Lingkungan, 2015)
Malaria is a disease which poses a health problem that can not be resolved completely. The incidence of malaria associated with those characteristics, environmental conditions and circumstances of the time. Bontobahari is one of the Districts in the region Bulukumba the case of malaria is high and volatile. The purpose of this study was to determine the spatial distribution of the incidence of malaria in Puskesmas Bontobahari sub-district Bontobahari of Bulukumba district.This type of research is an observational study with a descriptive approach. Population is all malaria patients from years 2012-2014 and the sample was taken by total sampling amounted to 21 respondents. Address mapping in patients using Global Positioning System (GPS).The results showed as much as 95.2% respondents are male, 38.1% of respondents aged 20-29 years, 47.6% of respondents have secondary education, 47.6% of respondents working as self-employed, where the majority of patients live in the Village Land Lemo, 100% of respondents residing ≤ 200 meters above sea level, 66.7% of respondents have access to health services as far as the location of ≥ 5 km, 76.2% of respondents exposed to Plasmodium vivax, as many as 76.2% of respondents do not have the contact history, 42.9% of respondents experienced a malaria hospital for 2 weeks, 66.7% of respondents have a habit of sleep at night without the use of mosquito nets and mosquito repellent. Conclusion of the study was the incidence of malaria in Puskesmas Bontobahari years 2012 - 2014 were the highest in the Tanah Lemo Village with most patients male sex. It is expected that the extension of the house to the house of the impact of malaria and can benefit from use of mosquito nets and mosquito repellent during sleep to reduce the number of the spread of malaria. Keywords : Malaria, spatial distribution, Bontobahari, Bulukumba, GPS